by user10511500
Last Updated October 16, 2018 09:20 AM

Reading algorithms. fibonacci example.

I saw an example where it said F(1) =1 and F(0) = 0. (fibonacci)

Why F(1) =1 and F(0) = 0? From where does it originate?

Thanks.

The initialization with $F(0)=F(1)=0$ is pretty fine. The recursion $F(n+1) = F(n)+F(n-1)$ for $n\geq 1$ gives $F(2)=1$, $F(3)=2$ and so on. This definition defines the sequence $(F(n))_n$ for all $n\geq 0$. The sequence is 0,1,1,2,3,5,8, and so on. It can also be written without the initial term: 1,1,2,3,5,8, and so on.

- ServerfaultXchanger
- SuperuserXchanger
- UbuntuXchanger
- WebappsXchanger
- WebmastersXchanger
- ProgrammersXchanger
- DbaXchanger
- DrupalXchanger
- WordpressXchanger
- MagentoXchanger
- JoomlaXchanger
- AndroidXchanger
- AppleXchanger
- GameXchanger
- GamingXchanger
- BlenderXchanger
- UxXchanger
- CookingXchanger
- PhotoXchanger
- StatsXchanger
- MathXchanger
- DiyXchanger
- GisXchanger
- TexXchanger
- MetaXchanger
- ElectronicsXchanger
- StackoverflowXchanger
- BitcoinXchanger
- EthereumXcanger